2012
DOI: 10.1523/jneurosci.0626-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Irrational Choice under Uncertainty Correlates with Lower Striatal D2/3Receptor Binding in Rats

Abstract: Individual differences in dopamine (DA) signaling, including low striatal D 2/3 receptors, may increase vulnerability to substance abuse, although whether this phenotype confers susceptibility to nonchemical addictions is unclear. The degree to which people use "irrational" cognitive heuristics when choosing under uncertainty can determine whether they find gambling addictive. Given that dopaminergic projections to the striatum signal reward expectancy and modulate decision-making, individual differences in DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 60 publications
(27 reference statements)
8
56
0
Order By: Relevance
“…From these findings, it is tempting to speculate that individual differences in riskier vs risk-averse patterns of decision making and corresponding differences in sensitivity to nonrewarded choices may be driven in part by variations in basal levels of D2 receptor activity within the BLA. This idea is in keeping with recent reports that individual differences in decision making under conditions of reward uncertainty are correlated to striatal D 2 receptor density, with lower levels of these receptors associated with greater sensitivity to how reward magnitudes modified choice biases (Cocker et al 2012). The present findings suggest that within the BLA, lower levels of D 2 receptor activity may be associated with reduced sensitivity to negative feedback.…”
Section: Da Receptor Stimulationsupporting
confidence: 85%
“…From these findings, it is tempting to speculate that individual differences in riskier vs risk-averse patterns of decision making and corresponding differences in sensitivity to nonrewarded choices may be driven in part by variations in basal levels of D2 receptor activity within the BLA. This idea is in keeping with recent reports that individual differences in decision making under conditions of reward uncertainty are correlated to striatal D 2 receptor density, with lower levels of these receptors associated with greater sensitivity to how reward magnitudes modified choice biases (Cocker et al 2012). The present findings suggest that within the BLA, lower levels of D 2 receptor activity may be associated with reduced sensitivity to negative feedback.…”
Section: Da Receptor Stimulationsupporting
confidence: 85%
“…This is an important departure from prior iterations of this task (Cocker et al, 2012;Nasrallah et al, 2009), which have relied on a step-wise reduction in the probability of risky reward across sessions. Our version of the task reduces the potential role of impaired behavioral flexibility on task performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has also shown that acute administration of dopamine antagonists effectively modified reward related behaviors such as gambling (Tremblay et al, 2010) and instrumental learning (Eisenegger et al, 2014;Pessiglione et al, 2006). In rats decision-making under uncertainty was influenced by a striatal D2/3 receptor antagonist, increasing risk aversion (Cocker et al, 2012;St Onge and Floresco, 2009). A proposed mechanism for these effects has been to consider dopamine a neurotransmitter driving motivation towards rewards (Berridge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%